Population structure of the intertidal crab Cyrtograpsus altimanus (Brachyura: Varunidae) in a northern Patagonia mussel bed - Vázquez, María Guadalupe (2012)
The population structure, size at maturity, reproductive period, recruitment and habitat use were studied in a population of the grapsoid crab Cyrtograpsus altimanus in an intertidal mussel bed at San Antonio Bay, Argentina. Samples were taken from October 2000 to January 2002. Crabs were sized and sexed to estimate size-frequency distributions (SFD). Modal groups of males and females were the same. Growth, evidenced by the shift to right of SFD modal classes, was observed in spring, summer and autumn. Size at maturity of females varied seasonally. Ovigerous females were found in winter, spring and summer, but two discrete recruitment events (in spring and autumn) are proposed. Based on the maximum male and female sizes found in the mussel bed, a size constraint is proposed that forces large crabs to migrate to cobblestone adjacent habitats.